Spectrofluorimetric Determination of Bicalutamide in Formulation and Biological Fluids - Anton Smith, A.; Manavalan, R.; Kannan, K.; Rajendiran, N. (Asian Journal of Chemistry, 2010)
A simple and reliable spectrofluorimetric method has been developed for the determination of bicalutamide in the pharma-ceutical preparation and biological fluids. The fluorescence of the product was found to have excitation at λmax 272 nm and emission λemi at 328 nm. The method shows high sensitivity with linearity range from 0.1 to 0.6 μg/mL. The lower limit of detection (LOD) was found to be 5.264 × 10-3 μg/mL, 9.55 × 10-3 μg/mL and limit of quantification (LOQ) was found to be 1.595 × 10-2 μg/mL, 2.893 × 10-2 μg/mL in formulation and biologfical fluids, respectively. The different experimental parameters affecting the fluorescence intensity were carefully studied and optimized. The proposed method was applied successfully for determination of bicalutamide in the pharmaceutical preparation and biological fluids. The percentage recovery was found to be 98.279 ± 0.35; 99.98 ± 2.012 for formulation and biological fluids, respectively.